2011
DOI: 10.1074/jbc.m110.168831
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1/Carbon Monoxide Induces Vascular Endothelial Growth Factor Expression via p38 Kinase-dependent Activation of Sp1

Abstract: Heme oxygenase-1 (HO-1) is a stress-inducible enzyme catalyzing the oxidative degradation of heme to free iron, CO, and biliverdin. Previous studies demonstrated that HO-1 overexpression promoted VEGF expression and angiogenesis in the ischemic heart. However, the underlying mechanism remained elusive. Here we show that adenovirus-mediated HO-1 transduction of rat primary cardiomyocytes and H9C2 myocytes resulted in significant induction of VEGF expression, and a similar effect was seen in cells directly expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 27 publications
2
40
0
1
Order By: Relevance
“…In the present study, we also determined that LPSdependent SIGIRR down-regulation seems due to inhibition of Sp1-dependent SIGIRR basal expression in monocytic and neutrophilic cells by using primary cells and cell lines. Moreover, our findings emphasized that LPS-activated p38 contributes to suppress Sp1-dependent SIGIRR basal expression, although generally p38 have been assumed to be a positive regulator of Sp1 (23,24). Thus, our findings are the first to show a negative regulatory role of p38 on Sp1-dependent transcription.…”
Section: Discussionmentioning
confidence: 52%
“…In the present study, we also determined that LPSdependent SIGIRR down-regulation seems due to inhibition of Sp1-dependent SIGIRR basal expression in monocytic and neutrophilic cells by using primary cells and cell lines. Moreover, our findings emphasized that LPS-activated p38 contributes to suppress Sp1-dependent SIGIRR basal expression, although generally p38 have been assumed to be a positive regulator of Sp1 (23,24). Thus, our findings are the first to show a negative regulatory role of p38 on Sp1-dependent transcription.…”
Section: Discussionmentioning
confidence: 52%
“…The transcription expression of the integrin ␣ V subunit gene is commonly controlled by transcriptional factors, among which Sp1 has binding sites in the integrin ␣ V subunit gene promoter, and phosphorylation on threonine 739 was enhanced after sulfatide stimulation. Sp1 mediates its target genes and can change its activity by phosphorylation on threonine 739 ( 36 ). Regarding the integrin ␣ V subunit, Sp1 promoted its expression by enhanced binding activity to the promoter because Sp1 protein was phosphorylated and its expression was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…This fi nding demonstrated that Erk1/2 signaling activation is important in Sp1 phosphorylation and integrin ␣ V subunit expression regulation by sulfatide. Activated p38 can also phosphorylate Sp1 on threonine 739 ( 36 ). Thus, activation of p38 contributes to the phosphorylation and activation of Sp1 as well, although the phosphorylation of p38 (T180/Y182) was not as robust as Erk1/2.…”
Section: Sulfatide Regulation Is Associated With Erk Signalingmentioning
confidence: 99%
“…We have highly plausible explanations to establish the link between the two. For example, it is well known that HO1 is an inducer of vascular endothelial growth factor (VEGF) (Cisowski et al, 2005; Lin et al, 2011), which is not only a promoter of angiogenesis but also has neurogenic properties (Sun et al, 2003). Thus HO1 seems to act on the neurovascular niche that supports the newly formed neurons as well as the vasculature surrounding the network.…”
mentioning
confidence: 99%